Difusi Inovasi Chatbot Vanrita dalam Komunikasi Pelayanan Kesehatan di RSUD Daya Makassar - Muris, Dendy; Dewi, Rima Kusumah (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
This study examines the digital innovation “Vanrita” chatbot (Virtual Assistant Balla Garring Ta) as a form of public communication transformation at Daya Public Hospital, Makassar. The research addresses the gap between Indonesia’s national digital health vision and the limited technological adoption in local public hospitals. The study aims to analyze user acceptance of Vanrita, factors influencing adoption decisions, and the relevance of this innovation to service efficiency and quality. A qualitative case study was conducted through in-depth interviews with 14 participants, including medical staff, public relations officers, and patients. Guided by Rogers’ Diffusion of Innovation Theory (2003), four dimensions were analyzed: innovation elements, characteristics, innovation process, and adopter categories. Findings reveal that Vanrita demonstrates strong relative advantage, high cultural compatibility, and low complexity, contributing to faster adoption among digitally literate users. However, adoption remains limited among elderly and non-digital users. The study concludes that effective interpersonal communication, sustained promotion, and institutional support are essential for strengthening the diffusion of digital innovations in public healthcare communication.